2012
DOI: 10.1007/s12011-012-9360-6
|View full text |Cite
|
Sign up to set email alerts
|

Zinc, Copper, Iron, and Chromium Concentrations in Young Patients with Type 2 Diabetes Mellitus

Abstract: Homeostasis of trace elements can be disrupted by diabetes mellitus. On the other hand, disturbance in trace element status in diabetes mellitus may contribute to the insulin resistance and development of diabetic complications. The aim of present study was to compare the concentration of essential trace elements, zinc, copper, iron, and chromium in serum of patients who have type 2 diabetes mellitus (n = 20) with those of nondiabetic control subjects (n = 20). The serum concentrations of zinc, copper, iron, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
6
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(83 citation statements)
references
References 26 publications
8
63
6
6
Order By: Relevance
“…Epidemiological studies also demonstrated that diabetes and whole body zinc status are associated [8][9][10][11]. In T1D and T2D patients, serum zinc levels are significantly decreased [9][10][11], this being associated with an increased zinc urinary loss [8].…”
Section: Zinc and The Diabetic Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies also demonstrated that diabetes and whole body zinc status are associated [8][9][10][11]. In T1D and T2D patients, serum zinc levels are significantly decreased [9][10][11], this being associated with an increased zinc urinary loss [8].…”
Section: Zinc and The Diabetic Patientmentioning
confidence: 99%
“…In T1D and T2D patients, serum zinc levels are significantly decreased [9][10][11], this being associated with an increased zinc urinary loss [8].…”
Section: Zinc and The Diabetic Patientmentioning
confidence: 99%
“…Epidemiological studies also suggest that whole body zinc status might be associated with diabetes (38,39) . Studies on patients with type 2 diabetes (T2D) revealed that the serum concentration of zinc was decreased compared with healthy control subjects (40,41) , a finding associated with increased urinary zinc loss (38) . Adequate levels of Zn 2+ are essential not only to ensure appropriate synthesis, storage and structural stability of insulin (42) but also to protect against oxidative stress in T1 and T2 diabetes and their associated pathologies (43) .…”
Section: Zinc and Diabetesmentioning
confidence: 99%
“…Published by Sciedu Press Basaki, year of data collection not reported [22] 40 female subjects referred to Dr. Saeb's specialized hormone lab (20 Nasli-Esfahani, year of data collection not reported [29] 301 participants: diabetic patients (n=150) and healthy controls (n=151). Tadayon , year of data collection not reported [32] 100 women between 35 to 70 years of age Tehran Hair…”
Section: Resultsmentioning
confidence: 99%
“…[64] Nour Mohammadi et al in Semnan showed that, Cr levels of hair samples in diabetes type 2 patients was significantly higher than controls (20 healthy volunteers). [21] In contrast, studies from Tehran, [29,32] Shiraz, and Tabriz, [22,24] showed Cr in diabetic type 2 patients were significantly lower than controls. Likewise, Kazi et al in Pakistan showed, Cr concentrations of hair and blood samples in diabetes type 2 patients were significantly lower than controls.…”
Section: Environmental Exposure To Crmentioning
confidence: 99%